2021
DOI: 10.21037/jtd-20-1968
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive aortic valve surgery

Abstract: Since their introduction, it has been demonstrated that minimally invasive aortic valve replacement (MIAVR) approaches are safe and effective for the treatment of aortic valve diseases. To date, the main advantage of these approaches is represented by the reduced surgical trauma, with a subsequent reduced complication rate and faster recovery. This makes such approaches an appealing choice also for frail patients [obese, aged, chronic obstructive pulmonary disease (COPD)]. The standardization of the minimally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
0
14
0
1
Order By: Relevance
“…In addition, the presence or absence of sternal fractures may play an important role in early postoperative pain levels. Additionally, we have drawback in our study that actually pain management was not standardized for all patients (12) .…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the presence or absence of sternal fractures may play an important role in early postoperative pain levels. Additionally, we have drawback in our study that actually pain management was not standardized for all patients (12) .…”
Section: Discussionmentioning
confidence: 95%
“…In 1996, Konertz et al first reported the AVR through the small incision of the upper sternum ( 8 ), many cardiac surgeons tried one after another, and the shape of the sternum incision gradually evolved from the “T” and “V” shape to the classic “J” shape or reverse. The “L” shape has become the most used minimally invasive AVR surgery ( 9 ). However, although these surgeries avoid full incision of the sternum, they still destroy the stability of the sternum.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally Invasive Aortic Valve Replacement [29][30][31][32][33] The Perceval facilitates aortic valve replacement through smaller incisions by eliminating the need for placing and tying sutures with limited exposure. Unlike transcatheter approaches, the Perceval allows direct visualization of the valve, appropriate decalcification of the annulus, and controlled direct deployment.…”
Section: Commandment 9: Use Adaptations To Surgical Techniques When P...mentioning
confidence: 99%